INTERPERSONAL BEHAVIORAL QUALITY RELATIONS: THE BULLYING BEHAVIORAL CASE AND THE EMOTIONAL AND SOCIAL SKILLS OF YOUNG PORTUGUESE STUDENTS - Bizai, Maria Eugénia (2017)
The quality of the interpersonal relationships that are established during the life is an important factor of psychological and social adjustment, indispensable for the human development. As adolescents dissociate themselves from their parents (although the family continues to occupy an important place) peer relationships increase, gain importance, and become the most influential context in terms of socialization. The school is one of the main scenarios structured to promote the personal development of each student, their capacities, learning and quality interactions with their colleagues. If school and peer acceptance are of great significance to adolescents, then not liking it or being rejected by peers can also lead to difficulties of social and emotional adjustment. Aggressive behaviors among peers are thus the main problem of interpersonal relationships in school context. Violent behaviors and situations of indiscipline are also frequently observed in school, but bullying is distinguished from these by evidence of an intentionality in aggression, by the regularity with which they occur (regardless of the form that occurs: direct, through physical or verbal aggression, or indirect, through relational aggression) and power imbalance among the participants. In this sense, this study intends to understand how aggressive behaviors among peers relate to the emotional and social skills of the students involved. To do this, a questionnaire survey was carried out through the Interpersonal Behavior Scale in School Context (ECICE) and the Bar-On Emotional Intelligence Questionnaire (EQ-i: YV), with 297 Portuguese students from a public school of the district of Évora - Portugal. The results show the existence of negative relations between the behaviors of bullying and the emotional and social competences. It was also possible to verify statistically significant differences in bullying situations and emotional and social competences, as a function of sociodemographic variables and school characterization. It is outlined the importance of the education of emotional and social competences for the promotion of quality interpersonal relationships in the school context.